Microstructural effects on fatigue crack growth behavior of a microalloyed steel - Laurito, D. F.; Baptista, C. A R P; Torres, M. A S [UNESP]; Abdalla, A. J. (Elsevier, 2010)
Thermal transformations on microalloyed steels can produce multiphase microstructures with different amounts of ferrite, martensite, bainite and retained austenite. These different phases, with distinct morphologies, are determinant of the mechanical behavior of the steel and can, for instance, affect the crack path or promote crack shielding, thus resulting in changes on its propagation rate under cyclic loading. The aim of the present work is to evaluate the effects of microstructure on the tensile strength and fatigue crack growth (FCG) behaviour of a 0.08%C-1,5%Mn (wt. pct.) microalloyed steel, recently developed by a Brazilian steel maker under the designation of RD480. This steel is being considered as a promising alternative to replace low carbon steel in wheel components for the automotive industry. Various microstructural conditions were obtained by means of heat treatments followed by water quench, in which the material samples were kept at the temperatures of 800, 950 and 1200 °C. In order to describe the FCG behavior, two models were tested: the conventional Paris equation and a new exponential equation developed for materials showing non-linear FCG behavior. The results allowed correlating the tensile properties and crack growth resistance to the microstructural features. It is also shown that the Region II FCG curves of the dual and multiphase microstructural conditions present crack growth transitions that are better modeled by dividing them in two parts. The fracture surfaces of the fatigued samples were observed via scanning electron microscopy in order to reveal the fracture mechanisms presented by the various material conditions. © 2010 Published by Elsevier Ltd.
Keywords: Fatigue crack growth; Heat treatment; Microalloyed steels; Microstructural analysis; Crack growth; Crack paths; Crack-growth resistance; Cyclic loadings; Exponential equations; Fatigue crack growth behavior; Fracture mechanisms; Fracture surfaces; In-wheel; Material conditions; Mechanical behavior; Microalloyed Steel; Microstructural conditions; Microstructural effect; Microstructural features; Multiphase microstructure; Non-linear; Paris equations; Propagation rate; Retained austenite; Steel-maker; Thermal transformations; Water quench; Automotive industry; Bainitic transformations; Fatigue crack propagation; Fatigue of materials; Fracture; Low carbon steel; Manganese; Manganese compounds; Martensitic steel; Metal analysis; Microstructural evolution; Scanning electron microscopy; Steel metallography; Tensile strength; Cracks